THE INTEGRATION OF VR TECHNOLOGY IN EARLY CHILDHOOD EDUCATION: REVIEW OF IMPACTS AND CHALLENGES - Liu, Ningyu; Wang, Xinyi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This systematic review explores the integration of Virtual Reality (VR) technology in early childhood education (ECE) in China, with the aim of identifying its pedagogical impacts, implementation challenges, and ethical considerations. Method: Guided by the PRISMA framework, a comprehensive search was conducted across CNKI, Wanfang, and ScienceNet databases using targeted keywords related to ECE, VR technologies, and preschool-aged children. Eighteen empirical and conceptual studies published between 2019 and 2023 were selected for thematic analysis. Results: Findings reveal that VR enhances children's learning engagement, enriches instructional contexts through immersive simulations, and supports personalized learning paths with real-time feedback. However, challenges include potential risks to visual health, developmental appropriateness of content, and limited teacher preparedness. Ethical concerns such as overreliance on virtual experiences and weakened emotional development were also noted. Novelty: This review contributes novel insights by offering a China-specific synthesis of current VR applications in preschool education, emphasizing the importance of establishing age-specific technical standards, interdisciplinary content development, and policy safeguards. The study calls for a balanced “virtual-reality complementarity” approach to align technological innovation with holistic child development.